Intensity and Incidence of Pest Disease Attacks on Rice Plants in Enggal Rejo Village, Air Salek Subdistrict - Wagiyanti Wagiyanti; Harman Hamidson; Suwandi Suwandi (Journal of Global Sustainable Agriculture, 2024)
Rice (Oryza sativa L.) is the main food crop widely cultivated by the people of Indonesia which has an important role in economic improvement. However, in the cultivation of rice plants, there are obstacles to the attack of pests and diseases that can reduce productivity both in quality and quantity. The purpose of this study was to determine the main pests and diseases that exist in rice plants and some incidence and intensity of attacks to minimize the control process. The research was conducted from November 2023 to February 2024. The observation method used diagonal sampling with 5 subplot points with one plot of 10 clumps of rice plants. Data were analyzed descriptively. The results showed that the main pest that attacked rice plants was the Rice Stem Borer with an attack rate of 13% categorized as a mild attack. While the main diseases found are panicle blast in the medium category, and leaf blast with the level of attack there are various phases of rice plant growth with mild to moderate categories, and midrib rot with mild categories.